The Inter-rater Reliability of the Functional Movement Screen Within an Athletic Population Using Untrained Raters. Issue 9 (September 2016) - Leeder, Jade. E; Horsley, Ian G.; Herrington, Lee C
Abstract : Abstract: Elias JE. The inter-rater reliability of the functional movement screen within an athletic population using untrained raters. J Strength Cond Res 30(9): 2591–2599, 2016—The functional movement screen (FMS) is a commonly used screening tool designed to identify restrictions to movement patterns and increased injury risk using 7 predesigned tests. The purpose of this study was to analyze the inter-rater reliability of scoring of the FMS using a group of "untrained" subjects. Additionally, the study also examined if clinical experience level had any effect on reliability. Twenty fully qualified Physiotherapists working at the English Institute of Sport, with elite athletes, volunteered to participate in the study. The group comprised both level 2 and level 3 physiotherapists based on clinical experience levels. Five elite athletes, free from injury, were recruited and videoed completing 6 of the 7 FMS tests using a 3 camera system. The videos were scored by each Physiotherapist using the standardized scoring sheet, as developed by Cook et al. Each practitioner marked each athlete completing the 6 tests. The total scores were calculated for each athlete (maximum score of 18). The inter-rater reliability of the test was shown to be high, intraclass coefficient 0.906. An independent t test showed no significant differences between the level 2 and level 3 practitioners in the total scores ( p = 0.502). The results of the test indicate that the FMS is a reliable screening tool when used by untrained practitioners in determining faulty movement patterns and that clinical experience level does not affect the reliability, therefore it may be a useful tool in the screening of athletic populations.